Effect of age on anthropometric and physical performance measures in professional baseball players - Mangine, G. T.; Hoffmann, J. R.; Fragala, M. S.; Vazquez, J.; Krause, M. C.; Gillet, J.; Pichardo, N. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to investigate age-related changes in anthropometric and performance variables in professional baseball players. Baseball players (n = 1,157) from several professional baseball organizations were categorized into 7 cohorts based upon age. All adolescent athletes were categorized as age group 1 (AG1), whereas the next 5 groups (AG2-AG6) consisted of players 20-22, 23-25, 26-28, 29-31, and 31-34 years, respectively. The final group (AG7) comprised athletes ?35 years. All performance assessments were part of the athlete's normal preseason training camp testing routine. Field assessments were used to analyze lower-body power, speed, agility, grip strength, and body composition. The players were heaviest between the ages of 29 and 31 (AG5), and their body mass in that age group was 10.1% (p = 0.004) greater than that of AG1. A 7.0% increase (p = 0.000) in lean body mass occurred between AG1 and AG5. No differences in 10-yd sprint times or agility were seen across any age group or position. A 2.0 seconds (p = 0.001) slower run time for the 300-yd shuttle was seen between AG4 and AG5 for all positions combined. Elevations in grip strength were seen at AG4 compared with AG1 (p = 0.001) and AG2 (p = 0.007) for all positions combined. No other differences were noted. Lower-body power was increased for all positions combined from AG1 to AG3 (p = 0.007). This pattern was similar to that observed in position players, but a 12.4% decrease (p = 0.024) in VJMP was seen between AG7 and AG5 in pitchers. Results of this study indicate that lower-body power is maintained in baseball players until the age of 29-31, whereas speed, agility, and grip strength are maintained in players able to play past the age of 35 years. Age-related differences observed in this study suggest that athletes focus on their strength and conditioning programs to extend the length of their professional careers.